Was Kuznets right? New evidence on the relationship between structural transformation and inequality - Çinar Baymul; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
We examine the Kuznets postulate that structural transformation leads to higher inequality using comparable panel data for a large number of developing and developed countries for 1960-2012. Countries are in different stages of structural transformation, being either structurally under-developed, structurally developing or structurally developed. In contrast to the Kuznets hypothesis, we find that the movement of workers to manufacturing unambiguously decreases income inequality, irrespective of the stage of structural transformation that a particular country is in. We also find that the movement of workers into services has a positive impact on inequality across our set of countries at an early stage of structural transformation and a negative effect at a later stage, suggesting that the Kuznets postulate may apply more for services driven structural transformation than manufacturing driven structural transformation. Overall, our findings confirm the positive development effects that structural transformation relating to manufacturing may have in developing countries, not merely through higher growth but by reducing inequality as well. However, for many low-income countries, where the realistic possibility of structural transformation may be the movement of workers from agriculture to services, our findings suggest that inequality may increase with further structural transformation.
Keywords: O11; O14; P51; 330; structural transformation; inequality; Kuznets; double dividend; manufacturing; services